Cerebrospinal fluid abacavir concentrations in HIV‐positive patients following once‐daily administration. (15th March 2018) - Calcagno, A.; Pinnetti, C.; De Nicolò, A.; Scarvaglieri, E.; Gisslen, M.; Tempestilli, M.; D'Avolio, A.; Fedele, V.; Di Perri, G.; Antinori, A.; Bonora, S.
Abstract : Abacavir is a widely used nucleotide reverse transcriptase inhibitor, for which cerebrospinal fluid (CSF) exposure has been previously assessed in twice‐daily recipients. We studied abacavir CSF concentrations in 61 and nine HIV‐positive patients taking abacavir once daily and twice daily, respectively. Patients on once‐daily abacavir had higher plasma and CSF concentrations (96 vs . 22 ng ml −1, P = 0.038 and 123 vs . 49 ng ml −1, P = 0.038) but similar CSF‐to‐plasma ratios (0.8 vs . 0.5, P = 0.500). CSF abacavir concentrations were adequate in patients receiving once‐daily treatment.